Comparative analysis of the anthropometric indices between Malay obese attributes and normal healthy individuals - Atif, Amin Baig; Mohd Khairi, Zahri@Johari; Ahmad Zubaidi, A.latif; Nordin, Simbak; Norizan, Abdul Ghani (2017)
Recently, globosity has become an alarming problem for health. The comparative anthropometric measurements between obese and normal healthy individuals are of great importance for the the underlying pathology associated with obesity. The objective was to compare means of anthropometric measurements between normal and obese healthy Malays. A cross sectional study was conducted, comprising of a total of 400 samples recruited through volunteer random sampling. A total of 95 subjects [male = 44 (46.3%) and females = 51 (53.7%); Age: 19 – 60 years], were included for the analysis for being the obese individuals as per inclusion criterion beside a total of 123 normal healthy subjects [male = 32 (26.0%) and females = 91 (74.0%); Age: 19 – 60 years]. Classical anthropometric measurements (waist circumference, hip circumference, body mass index (BMI), waist to hip ratio (WHR) and body fat percentage (Fat %) were determined beside determination of a novel ASindex [hip – waist (cm)]. The mean values of BMI, ASindex [hip – waist (cm)], waist to hip ratio (WHR) and body fat% were determined and compared to see the difference between obese and normal healthy individuals.The comparative analysis was performed and the results were represented as mean. The mean of the BMI, WHR, Fat% and ASindex, in Malay obese attributes were calculated to be 32.83, 0.88, 33.5 and 13.21 respectively. Similarly, the mean of the BMI, WHR, Fat% and ASindex, in normal healthy individuals were calculated to be 22.1, 0.78, 24.2 and 20.1 respectively. The difference of mean of BMI, WHR, Fat% and ASindex was calculated to be 10.73, 0.1, 9.3 and 6.89 respectively.To the best of our knowledge, this is the first report in Malaysia; comparing mean values of BMI, WHR, Fat% and ASindex are clearly indicating the difference of mean in obese and normal healthy individuals in Malay attributes.